Family Ties in Entrepreneurs’ Social Networks and New Venture Growth - Arregle, Jean–Luc; Batjargal, Bat; Hitt, Michael A.; Webb, Justin W.; Miller, Toyah; Tsui, Anne S. (Entrepreneurship Theory and Practice, 2015)
Family ties are an important conduit of resources for entrepreneurs, but both positive and negative outcomes can arise. Building upon a family embeddedness perspective, we develop hypotheses about curvilinear relationships between the proportion of family ties in entrepreneurs’ networks and venture growth. We test them on entrepreneurs from China, France, Russia, and the United States. These effects appear to be related to the type of entrepreneurs’ social network (business advice, emotional support, and business resources). Our results confirm effects specific to each network: an inverted U–shape for advice and emotional support networks but a U–shape for the business resource network, measuring what proportion of kin in each entrepreneurial network type is valuable to or, conversely, undermines new venture growth.